2022
DOI: 10.1001/jamanetworkopen.2022.42666
|View full text |Cite
|
Sign up to set email alerts
|

Small Area Variation in the Quality of Maternal and Newborn Care in India

Abstract: ImportanceIn India, the district serves as the primary policy unit for implementing and allocating resources for various programs aimed at improving key developmental and health indicators. Recent evidence highlights that high-quality care for mothers and newborns is critical to reduce preventable mortality. However, the geographic variation in maternal and newborn health service quality has never been investigated.ObjectiveTo examine the variation between smaller areas within districts in the quality of mater… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 31 publications
0
10
0
Order By: Relevance
“…We also found that cluster variation was substantial across all selected states. A recent study that attempted to partition the geographic variation in a composite score of maternal health care quality in India had similar results (VPC for clusters = 58.3%, states/union territories = 29.3%, and districts = 12.4%), indicating the relative importance of clusters in reducing geographic inequalities for overall maternal health care quality in India [ 18 ]. Although the Indian government adopted the Reproductive, Maternal, Newborn, Child, and Adolescent Health (RMNCH + A) framework to improve maternal and child health since 2013 [ 46 ], the intervention undertaken within have mainly been focussed at the district level [ 29 , 47 , 48 ].…”
Section: Discussionmentioning
confidence: 85%
See 2 more Smart Citations
“…We also found that cluster variation was substantial across all selected states. A recent study that attempted to partition the geographic variation in a composite score of maternal health care quality in India had similar results (VPC for clusters = 58.3%, states/union territories = 29.3%, and districts = 12.4%), indicating the relative importance of clusters in reducing geographic inequalities for overall maternal health care quality in India [ 18 ]. Although the Indian government adopted the Reproductive, Maternal, Newborn, Child, and Adolescent Health (RMNCH + A) framework to improve maternal and child health since 2013 [ 46 ], the intervention undertaken within have mainly been focussed at the district level [ 29 , 47 , 48 ].…”
Section: Discussionmentioning
confidence: 85%
“…To further advance the accumulating literature quantifying small area variation in various health outcomes in India [ 15 18 , 49 ], we assessed the extent to which total contextual variation in PNC utilisation at each geographic level can be explained by different compositional factors. When we simultaneously considered various demographic, socioeconomic, and pregnancy-related characteristics, we found maternal education, household wealth, health insurance, ANC visits, and delivery at private facilities to be statistically significant factors associated with maternal and newborn PNC utilisation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A 4-level logistic regression was estimated for each outcome using standard multilevel modeling [6][7][8][9][10][11][12][13][14] (eEquation 1 in Supplement 1), and variance partitioning coefficient (VPC) was calculated for each level (eEquation 2 in Supplement 1). In this study, we focused on the total geographic variability as opposed to total variability (including 3.29 as level 1 variance) to assess the relative importance of geographic levels.…”
Section: Discussionmentioning
confidence: 99%
“…4 For example, states are principal macro policy units, and districts are subdivisions of states that serve as central policy units for the development, administration, and implementation of programs. 5 However, prior studies have consistently demonstrated considerable variability across small areas for various development and health outcomes, [6][7][8][9][10][11][12][13][14] underscoring the significant inequality within any given district and raising concerns about the potential limitations of a one-size-fits-all approach based on district averages. These findings are primarily restricted to child-related issues, such as poor nutrition [8][9][10] and birth outcomes, [11][12][13] and there remains limited knowledge about small area variability in CVD risk factors among adults.…”
Section: Introductionmentioning
confidence: 99%